Application of DNA markers for detection of scab resistant apple cultivars and selections - Mattisson, H.; Nybom, H. (International Journal of Horticultural Science, 2005)
A DNA marker-based study was undertaken to identify the occurrence of major scab resistance genes in some apple cultivars and selections of importance for apple breeding. Unfortunately none of the RAPD-based markers previously reported to detect the Va, Vb, Vr and Vx genes produced unambiguous results. By contrast, the CAPS marker MI8 produced the expected three bands in all cultivars and selections already known or suspected to have the Vf gene, as well as in the Russian cultivar 'Antonovka Polotora Funtovaja' suspected to have Va resistance which however may be allelic to Vf. Vf-carrying selections and newly named cultivars 'Frida' and 'Fredrik' are grown successfully in Sweden without fungicides, suggesting that the Vr resistance breaking scab races 6 and 7 have not yet become a problem. The SCAR marker B12 detected the Vm gene in 'Prairifire', 'Rouville', clones 'OR45T132' and 'OR48T70', and selection '16-36-193'. The SSR locus 0102b10 detected one band at 118 by in 'Reka'. This is presumed to be identical to the Vr gene marker previously reported.